2015
DOI: 10.1103/physreva.92.062130
|View full text |Cite
|
Sign up to set email alerts
|

Steering criteria via covariance matrices of local observables in arbitrary-dimensional quantum systems

Abstract: We derive steerability criteria applicable for both finite and infinite dimensional quantum systems using covariance matrices of local observables. We show that these criteria are useful to detect a wide range of entangled states particularly in high dimensional systems and that the Gaussian steering criteria for general M × N -modes of continuous variables are obtained as a special case. Extending from the approach of entanglement detection via covariance matrices, our criteria are based on the local uncertai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…In this Article we demonstrate that there exist two-mode Gaussian states for which Gaussian measurements cannot manifest steering, but non-Gaussian measurements can. For this purpose, we employ a formulation of steering criterion based on local uncertainty relations involving non-Gaussian measurements 47 . We study steerability of mixed Gaussian states, specifically, Gaussian states under a lossy and an amplifying channel that represent typical noisy environments.…”
mentioning
confidence: 99%
“…In this Article we demonstrate that there exist two-mode Gaussian states for which Gaussian measurements cannot manifest steering, but non-Gaussian measurements can. For this purpose, we employ a formulation of steering criterion based on local uncertainty relations involving non-Gaussian measurements 47 . We study steerability of mixed Gaussian states, specifically, Gaussian states under a lossy and an amplifying channel that represent typical noisy environments.…”
mentioning
confidence: 99%
“…Since 2007, EPR-steering has been understood to make up part of a hierarchy of quantum correlations, situated between entanglement [ 81 , 82 ] and Bell non-locality [ 83 ]. In addition to methods utilizing variance-based URs [ 84 ], entropic URs, such as those in Section 2.2 , can be used to identify EPR-steering [ 85 , 86 ] and to quantify high-dimensional entanglement [ 87 , 88 ]. Some of these URs can be used to test security in continuous variable quantum cryptography [ 89 , 90 ], and it has been shown that violation of entropic EPR-steering criteria are directly related to the secret key rate in one-sided device independent cryptography [ 91 ].…”
Section: Utility Of Uncertainty Relations In Quantum Physicsmentioning
confidence: 99%
“…For example, Cavalcanti and James in [ 21 ] obtained the experimental criterion of EPR steering from entropy uncertainty relations. Ji et al in [ 22 ] obtained steerability criteria by using covariance matrices of local observables, which are applicable for both finite- and infinite-dimensional quantum systems. Wittmann et al in [ 23 ] gave EPR steering inequalities with three Pauli measurements; and then, as a generalization of the Pauli matrices, Marciniak et al in [ 24 ] found EPR steering inequalities with mutually unbiased bases.…”
Section: Introductionmentioning
confidence: 99%